Developing of a Multi-Project Planning and Control System for Risk-Based Precast Concrete Procurement to Increase PT. XY’s Competitiveness - Widiasih, Widiasih; Muslim, Fadhilah (Publisher Cv. Inara, 2024)
Multi-project planning and control must be part of the precast concrete industry to achieve more efficient project performance and impact obtaining better contract values. It requires a clear and detailed understanding of the project's scope and the risks in project planning. This research aims to analyze the risk factors that influence ongoing multi-project procurement and carry out risk-based development to increase the Competitiveness of PT XY. This research uses a methodology to study related literature, previous research, and PT Company Operational Standards. XY. The results of this study indicate that 7 out of 37 variables have high-risk values, while the remaining 30 are classified as having moderate Risk. The Risk of wage and material price increases represents the highest Risk in developing a multi-project planning and control system for precast concrete procurement to enhance the Competitiveness of PT. XY.